Przełamywanie granic książki dla dziecka. Ostatnie przedstawienie panny Esterki Adama Jaromira jako lektura o czytaniu pamięci - Michułka, Dorota (Dydaktyka Polonistyczna, 2016)
The Last Play by Miss Esterka (2014) belongs to the growing circle of literary texts for children about the Holocaust and the phenomenon of „post-memory” (including such texts as Pamiętnik Blumki by Iwona Chmielewska, 2014; Arka czasu, czyli wielka ucieczka Rafała od kiedyś przez wtedy do teraz i wstecz by Marcin Szczygielski, 2013; Dym by Antón Fortes and Joanna Concejo, 2011). In this case, going beyond the boundaries of a children’s book is achieved through the merge of aesthetic education (including art, literature, and theatre) and the formal interweavement of source texts from the past (letters, journals, calendar sheets, bills from everyday economy) with the author’s own commentary and the book’s rich visual aspect – its illustrations, which resemble photographs and collages, authenticate the text. This effect is reinforced with the book’s mature historical and philosophical context as well as references to three real-life role authorities: Janusz Korczak, Rabindranath Tagore, and Estera Winogron – Estera helps children from an orphanage organize a play based on Tagore’s The Post Office about a dying boy. Tagore was an Indian poet, mystic, prose writer, Nobel prize laureate, philosopher, composer, painter, teacher and educationalist – his theories and practices of „interdisciplinary education” were an inspiration to Janusz Korczak. In the creation of his „educational ideal”, Tagore emphasized the importance of art. He also believed that formation of the child should be based on respect for their individuality and spirituality, and should facilitate child’s self-improvement and self-discovery – which is consistent with Korczak’s position and manifests itself in Jaromir’s story.